2020
DOI: 10.1002/slct.202000107
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Laser‐Induced Breakdown Spectroscopy (LIBS) Data for the Determination of Cation Exchange Capacity (CEC) of Agricultural Soils

Abstract: The potential for Laser Induced Breakdown Spectroscopy (LIBS) technique to predict cation exchange capacity (CEC) values in agricultural soils, based on a partial least square (PLS) regression model, was investigated by analysing soils (N = 225) using a portable LIBS system. The prediction from the validation set was 0.75 and the RMSE was 5.4 cmol + /kg. Analysis of the PLS loading weights showed that emission lines that correlate with the exchangeable cations (Ca, Mg, K and Na) and clay (Al and Si) are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Huang 224 proposed a zircon megacryst (SA01-A) as a new RM for microbeam U-Pb geochronology and Hf and O isotope geochemistry. A mean 206 Pb/ 238 U age of 535.08 AE 0.32 Ma was determined by CA-ID-TIMS, a d 18 O value of 6.16 AE 0.26& by laser uorination and a mean 176 Hf/ 177 Hf ratio of 0.282293 AE 0.000007 by solution MC-ICP-MS. Although the megacryst was homogeneous for these measurements, it had signicant spatial variations in Th/ U and Li isotope ratios.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Huang 224 proposed a zircon megacryst (SA01-A) as a new RM for microbeam U-Pb geochronology and Hf and O isotope geochemistry. A mean 206 Pb/ 238 U age of 535.08 AE 0.32 Ma was determined by CA-ID-TIMS, a d 18 O value of 6.16 AE 0.26& by laser uorination and a mean 176 Hf/ 177 Hf ratio of 0.282293 AE 0.000007 by solution MC-ICP-MS. Although the megacryst was homogeneous for these measurements, it had signicant spatial variations in Th/ U and Li isotope ratios.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 99%
“…The practical lower limit for the 180 Hf intensity was set at ca. 1 V so that meaningful 176 Hf/ 177 Hf ratios and <1.5 3 unit internal errors could be achieved simultaneously. Zircon was also the focus of a study which reported 290 a protocol for in situ determinations of stable Zr isotope ratios by LA-MC-ICP-MS.…”
Section: Isotope Ratio Determinations By Icp-msmentioning
confidence: 99%
See 1 more Smart Citation